Pengaruh Digital Orientation dan Digital Transformation Terhadap Kinerja Operational UMKM Kota Padang Dimediasi Digital Innovation - Razi, Fakhrur; Linda, Muthia Roza (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Digital transformation is a crucial factor in enhancing the competitiveness of MSMEs, particularly in the supermarket and minimarket retail sectors, which face changing consumer behavior and increasingly dynamic business competition. This study aims to analyze the influence of Digital Orientation and Digital Transformation on the operational performance of MSMEs in Padang City, with Digital Innovation as a mediating variable. The study employed a quantitative approach with a survey method involving 148 owners or managers of supermarket/minimarket retail MSMEs selected using probability sampling based on the Krejcie and Morgan table from a population of 239 business units. Data were collected through a structured questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results showed that Digital Orientation and Digital Transformation had a positive and significant effect on Digital Innovation and operational performance. Furthermore, Digital Innovation had a positive effect on operational performance and was proven to mediate the effect of Digital Orientation on operational performance, but did not mediate the effect of Digital Transformation. These findings indicate that strengthening digital orientation followed by the development of digital innovation is an important factor in improving the operational performance of supermarket and minimarket retail MSMEs in Padang City.